The Institutional ESG Disclosure Framework for Malaysian Consultancy Quantity Surveying Practices: A Systematic Literature Review - Baharuddin, Dainna; Zainordin, Nadzirah; Jusoh, Zairra Mat (Journal of Ecohumanism, 2025)
Environmental, Social, and Governance (ESG) disclosure has emerged as a key indicator of corporate transparency and sustainability. Public listed companies in the construction industry in Malaysia are mandated to disclose ESG practices. However, there is no institutional framework specifically for quantity surveying firms namely Consulting Quantity Surveying Practice (CQSP). This study employs a Systematic Literature Review (SLR) to examine ESG disclosure practices relevant to CQSP, analyze global best practices, and propose a structured framework tailored for the Malaysian CQSP. The findings highlight challenges such as regulatory ambiguity, lack of industry-specific guidelines, and low awareness among QS professionals. Based on thematic analysis, a proposed ESG disclosure framework is developed, incorporating environmental, social, and governance dimensions relevant to CQSP. The study recommends policy enhancements by the QS regulatory body Board of Quantity Surveyors and QS professional body the Royal Institution of Quantity Surveyors Malaysia as well as QS firms, ensuring greater ESG transparency and compliance.